1996
DOI: 10.1108/03068299610122416
|View full text |Cite
|
Sign up to set email alerts
|

On the relativity of the concepts of needs, wants, scarcity and opportunity cost

Abstract: The concept of scarcity is the cornerstone of economics as a discipline. After all, "Economics is the study of how societies use scarce resources to produce valuable commodities and distribute them among different groups" (Samuelson and Nordhaus, 1989, p. 5). What is more, the economics profession is rather particular in distinguishing absolute from relative scarcity, and quick in emphasizing that it is relative scarcity which defines economics. Most of the current economic theory is derived from the law of (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Moreover, this study has also shown that the definitions of absolute and relative scarcity do not necessarily hinge upon the distinction between needs and desires (Baumgartner et al. 2006; Raiklin and Uyar 1996).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, this study has also shown that the definitions of absolute and relative scarcity do not necessarily hinge upon the distinction between needs and desires (Baumgartner et al. 2006; Raiklin and Uyar 1996).…”
Section: Discussionmentioning
confidence: 80%
“…These are, however, implicitly used in the literature and thus need to be further studied. Where this distinction is used explicitly, it mainly corresponds to the difference between human needs and desires (Baumgartner et al 2006; Raiklin and Uyar 1996). This article will argue that this correspondence is not a necessary condition to define these two views.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, critics of mainstream economic thought 1 have expressed alarm that this formulation may not adequately cover the phenomenon of scarcity (Bretschger, 2005;Baumgärtner et al, 2006;Daoud, 2011Daoud, , 2007Raiklin and Uyar, 1996;Sahu and Nayak, 1994). These scholars argue that mainstream economics limits itself to the study of phenomenon of "relative" scarcity, which already presupposes that "scarce" goods can be substituted for other goods or that more of the scarce good can be produced by reallocating resources differently (Baumgärtner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Raiklin and Uyar (1996) argue that eliminating the needs/wants distinction "has meant also that the moral and social implications of such comparisons and discussions could be kept out of economic theory and analysis. "…”
Section: Welfare Is Preference Satisfactionmentioning
confidence: 99%